MANFAAT ULVA LACTUCA SEBAGAI MASKER WAJAH ALAMI - Maulidya, Rulita; Handayani, Lia; Syahputra, Faisal; Thaib, Azwar; Mardhiah, Ainal (Yayasan Sagita Akademia Maju, 2024)
Cosmetic products in Indonesia are growing rapidly in this era of technological progress, so now cosmetics are synonymous with women, and men are also interested in skincare. However, due to the lack of knowledge about the function of the substances contained in a product whether it is good or not if used in cosmetic products. Apart from that, most people do not know how to utilize village potential. Making organic masks aims to avoid the dangers of instant masks and utilizing the potential of village natural resources is the right solution. Therefore, this community service activity can be used as education on organic masks based on utilizing the potential of Ulva lactuca seaweed. Organic masks are very safe from chemicals that can damage facial skin. Organic masks contain more nutrients that are good for facial skin and can be used by all facial skin types. The results of community service showed a low increase in the participants' understanding of knowledge.